PENGEMBANGAN BUKU AJAR STATISTIKA BERBANTUAN TIK DENGAN PENDEKATAN PENILAIAN PORTOFOLIO UNTUK MENINGKATKAN KOMUNIKASI DAN KONEKSI MATEMATIS - Hendikawati, Putriaji; Arini, Florentina Yuni (Jurnal Penelitian Pendidikan, 2016)
This research was development research that aimed to develop and produce a Statistics textbook model that supported with ICT and portfolio based assessment. This book was designed to improve students ability in communication and mathematical connections. There were three stages in this research i.e. define, design, and develop. The textbooks consisted of 10 chapters which each chapter contains introduction, core materials and include examples and exercises. The textbook developed phase begins with the early stages of designed the book (draft 1) which then validated by experts. Revision of draft 1 produced draft 2 which then limited test for readability test book. Furthermore, revision of draft 2 produced textbook draft 3 which simulated on a small sample to produced a valid model textbook. The data were analyzed with descriptive statistics. The analysis showed that the Statistics textbook model that supported with ICT and portfolio based assessment valid and fill up the criteria of practicality.